Maternal Cerebrospinal Fluid Glutamate in Response to Variable Foraging Demand: Relationship to Cerebrospinal Fluid Serotonin Metabolites in Grown Offspring. (July 2018) - Coplan, Jeremy D.; Gupta, Nishant K.; Flynn, Sarah K.; Reiner, Wade J.; Gaita, David; Fulton, Sasha L.; Rozenboym, Anna V.; Tang, Jean E.; Cooper, Thomas B.; Mann, J. John
Background: Maternal response to allostatic overload during infant rearing may alter neurobiological measures in grown offspring, potentially increasing susceptibility to mood and anxiety disorders. We examined maternal cerebrospinal fluid (CSF) glutamate response during exposure to variable foraging demand (VFD), a bonnet macaque model of allostatic overload, testing whether activation relative to baseline predicted concomitant CSF elevations of the stress neuropeptide, corticotropin-releasing factor. We investigated whether VFD-induced activation of maternal CSF glutamate affects maternal–infant attachment patterns and offspring CSF 5-hydroxyindoleacetic acid concentrations. Methods: Mother–infant dyads were exposed to the "VFD stressor, " a paradigm in which mothers experience 16 weeks of foraging uncertainty while rearing their infant offspring. Through staggering the infant age of VFD onset, both a cross-sectional design and a longitudinal design were used. Maternal CSF glutamate and glutamine concentrations post-VFD exposure were cross-sectionally compared to maternal VFD naive controls. Proportional change in concentrations of maternal glutamate (and glutamine), a longitudinal measure, was evaluated in relation to VFD-induced elevations of CSF corticotropin-releasing factor. The former measure was related to maternal–infant proximity scores obtained during the final phases of VFD exposure. Maternal glutamatergic response to VFD exposure was used as a predictor variable for young adolescent offspring CSF metabolites of serotonin, dopamine, and norepinephrine. Results: Following VFD exposure, maternal CSF glutamate concentrations correlated positively with maternal CSF CRF concentrations. Activation relative to baseline of maternal CSF glutamate concentrations following VFD exposure correlated directly with a) increased maternal-infant proximity during the final phases of VFD and b) offspring CSF concentrations of monoamine metabolites including 5-hydroxyindoleacetic acid, which was elevated relative to controls. Conclusions: Activation of maternal CSF glutamate in response to VFD-induced allostasis is directly associated with elevations of maternal CSF corticotropin-releasing factor. Maternal CSF glutamate alterations induced by VFD potentially compromise serotonin neurotransmission in grown offspring, conceivably modeling human vulnerability to treatment-resistant mood and anxiety disorders.